Kinship and gender as political processes among the Miskitu of eastern Nicaragua / Mark Angus Jamieson - Jamieson, Mark Angus (Mexico University of London, 1995)
This thesis is concerned with local concepts of kinship and personhood in a small Miss· illage named Kakabila in eastern Nicaragua, and examines how gender identities are orgarused around a culturally specific variant of the set of practices which anthropologists have glossed as 'bride service'. Personhood in Ka.kabila is focused on the establishment of a stable conjugal pannership. Men usually attach themselves to the households of their conjugal panners, and atternpt to legitimate their claims to their wives by uxorilocal postnuptial residence and the practice of long term brideservice. The central concem of many Ka.kabila men therefore is with demonstrating that they conduct themselves with their affines harmoniously in accordance with village ideals. For many men, ho wever, the eventual objective is to detach their wives from the influence of consanguine kin, and this produces a tension between the need to project affinal hannony and the concem that actions may be construed in terms of elopement. Kakabila women, however, tend to be much more concemed with constructing networks of symbolic exchange and mutual assistance among themselves, particularly with their consanguine! kinswomen. In many cases, therefore, women resist the attempts of husbands and sons-in-law to disrupt these networks, and organize their actions around ensuring that errant husbands and junior male affines adequately supply them with sufficient symbolic capital to adequately maintain and cultivare these networks, This thesis, therefore, suggests a very specific formulation of the logic of gender identities in Kakabila, where bride service is as much style of distribution as it is a 'sty le of conscription' (Collier and Rosaldo 1981: 27 5), based on a particular disjunction between men's and wornen's motivations. This thesis also considers the changes in Miskitu kinship in terms of changes which have taken place arming the Miskitu during the last three hundred years, particularly the marked trading and political imbalances brought about by long tern contact with the English speaking Caribbean countries. The disappearance of the historically attested distinction between cross and p3.LI e cousins and the serial exchange of offspring and siblings, and the emergence of u x ori postnuptial residence, are analyses in terms of J. gradual h1storical reformulation notions of affinity which owes a great deal to these regional contracts. An ethno ~ ~ historically informed analysis for these transformations 1s considered. why ·h m · shed light on gender identities and the practice of bride service in present da '
Table of contents, maps, table, graphs and bibliographic reference
Keywords: 1. DOMESTIC REALATIONESHIP 2. CONSAN GUINITY 3. KINSHIP-GENDER-POLITICAL 4. MISKITU-EASTERN NICARUGA 5. THESIS-ANTHROPOLOGY